GaSb film preparation method based on magnetron sputtering technology
By using ethanol, acetone and deionized water in magnetron sputtering method, controlling the sputtering conditions and performing annealing treatment in magnetron sputtering, the problem of difficult to control element components and cluster formation is solved in magnetron sputtering method to prepare GaSb films, and high-quality GaSb film preparation is achieved.
Patent Information
- Application Number
- CN202411713459.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-28
AI Technical Summary
Magneto-controlled sputtering method makes it difficult to control element components, and the fast sputtering rate can easily form clusters at the film interface.
The substrate is cleaned by ethanol solvent, acetone solution and deionized water, combined with ultrasonic cleaning to ensure the cleanliness of the substrate. The vacuum degree and temperature of the sputtering chamber are then controlled in a magnetron sputtering device, the GaSb target is sputtered on the surface of the gallium antimonide substrate using a radio frequency sputtering method, and annealing is performed to improve the crystallinity of the film.
The contaminants on the substrate surface are effectively removed, the surface state of the substrate is improved, the uniformity and adhesion of the film are ensured, the film defects and surface unevenness are avoided, and the composition uniformity and crystallinity of the GaSb film are improved.
Smart Images

Figure CN119710930A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of magnetron sputtering growth, and in particular to a method for preparing a GaSb film based on magnetron sputtering technology. Background Art
[0002] Gallium antimonide is a III-V semiconductor material with the characteristics of medium energy gap, high electron mobility, excellent photoelectric properties and adjustable band gap. Due to its small band gap energy, gallium antimonide can achieve efficient light absorption and detection between the mid-infrared band (2~5 μm) and the long-wave infrared band (8~12 μm). These characteristics make gallium antimonide have broad application prospects in infrared detection, imaging and high-power electronic devices.
[0003] As a direct bandgap semiconductor, GaSb has a small energy change in the process of photon absorption and radiation, and has high photon absorption efficiency, which makes it suitable for devices such as photodetectors, lasers and light-emitting diodes. The goal is to epitaxially grow high-quality GaSb thin films on GaSb substrates, and the quality of thin film growth can be changed by using epitaxial thin film growth methods and parameter control during the preparation process.
[0004] Compared with molecular beam epitaxy (MBE) and metal organic chemical vapor deposition (MOCVD) methods for epitaxial growth of GaSb thin films on GaSb substrates, magnetron sputtering has the advantages of relatively cheap equipment, simple material growth method, fast film formation rate, good film quality, and low cost. However, it is difficult to control the element composition of thin films prepared by magnetron sputtering, and too fast sputtering rate easily forms clusters at the film interface. Summary of the invention
[0005] One of the purposes of the present invention is to provide a method for preparing GaSb thin films based on magnetron sputtering technology to solve the problems in the prior art that it is difficult to control the element composition of thin films prepared by magnetron sputtering and that too fast sputtering rate easily forms clusters at the film interface.
[0006] The present invention is achieved by the following technical scheme: a method for preparing a GaSb thin film based on magnetron sputtering technology, comprising preparing a magnetron sputtering target material for standby use, soaking a gallium antimonide substrate in an ethanol solvent, using ultrasonic cleaning for 10 minutes, and then using deionized water to clean the gallium antimonide substrate for 10 minutes, and then soaking the gallium antimonide substrate in an acetone solution, using ultrasonic cleaning for 10 minutes, and then using deionized water to clean the gallium antimonide substrate for 10 minutes; sending the gallium antimonide substrate after cleaning into a magnetron sputterer, and controlling the vacuum degree of the sputtering chamber of the magnetron sputtering to 1.9×10 -4Pa, and at the same time, the temperature of the sputtering chamber is raised to 660 ° C and kept warm for 10 minutes; the temperature of the sputtering chamber is lowered to 450 ° C to sputter the target material on the surface of the gallium antimonide substrate, forming a GaSb film on the surface of the gallium antimonide substrate, and obtaining a GaSb film with a deposition thickness of 400~500 nm.
[0007] Furthermore, the magnetron sputtering target is a P-type GaSb target prepared by uniformly mixing simple Ga and Sb or a compound containing simple Ga and Sb in an atomic ratio of 1:1.
[0008] Furthermore, the gallium antimonide substrate is a single-side polished P-type single crystal gallium antimonide.
[0009] Furthermore, the sputtering target is sputtered by a radio frequency sputtering method.
[0010] Furthermore, the sputtering power of the magnetron sputtering device is 50~90 W, the sputtering time is 1~30 min, the growth temperature is 350~550 ℃, the working gas during sputtering is argon, the gas flow rate is 20~25 sccm, and the gas pressure is 0.5 Pa.
[0011] Furthermore, the preparation method may also include an annealing step, wherein the gallium antimonide substrate after magnetron sputtering is cooled to room temperature and then annealed.
[0012] Furthermore, the annealing operation can be performed in an argon atmosphere with a flow rate of 50-100 mL / min.
[0013] Furthermore, the annealing temperature is 450-650°C, the heating rate is 5-15°C / min, and the annealing time is 30-90 min.
[0014] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0015] 1. The present invention uses ethanol solvent, acetone solution and deionized water to clean the substrate, and adopts ultrasonic cleaning to effectively remove impurities such as pollutants, grease, dust and the like on the surface of the substrate, which is a key step to improve the quality of the film, helps to ensure the uniformity and adhesion of the film, and avoids film defects or surface unevenness caused by pollutants. At the same time, by heating the sputtering chamber to 660°C before sputtering and keeping it warm for 10 minutes, it helps to remove any residual pollutants on the surface of the substrate, and can also improve the surface state of the substrate, providing a clean and uniform base for thin film deposition.
[0016] 2. The present invention uses gallium (Ga) and antimony (Sb) or compounds containing them in an atomic ratio of 1:1 to make a target material, ensuring that the chemical composition of the target material is consistent with the composition of the target GaSb film. This precise atomic ratio ensures uniform composition of the film and avoids fluctuations in film performance caused by excessively uneven composition.
[0017] 3. The present invention uses a magnetron sputtering method to grow a high-quality GaSb thin film on a single crystal GaSb substrate through parameter control based on a small sputtering power and a reasonable annealing process. The magnetron sputtering technology is used to adjust the sputtering power and the substrate growth temperature to prepare a highly uniform film, and a suitable annealing process is used to improve the crystallinity and film quality of the GaSb film and reduce the defect density of the material layer. The method of the present invention has the characteristics of simple preparation process, fast sputtering rate, good film density, uniformity and repeatability. Through the method of the present invention, a high-quality GaSb thin film can be grown on a single crystal GaSb substrate, which has a great promotion effect on the material in the field of industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0019] Figure 1 This is a flowchart provided for Example 4 of the present invention.
[0020] Figure 2 1 is a Raman graph of the unannealed GaSb film at different growth temperatures under the condition of a sputtering power of 80 W in Example 4 of the experimental example of the present invention.
[0021] Figure 3 The Raman graphs of the unannealed GaSb film at different sputtering powers under the growth temperature of 450° C. in Example 4 of the experimental example of the present invention are shown.
[0022] Figure 4 The SEM images of the unannealed GaSb thin films of Example 4 in the experimental examples of the present invention are shown in FIG. 4 at a sputtering power of 80 W and growth temperatures of 400, 450, 500 and 550° C.
[0023] Figure 5 The Raman graphs of the GaSb thin film annealed at 450, 500, 550, 600 and 650 °C for 1 h in a tubular annealing furnace under the conditions of a growth temperature of 450 °C and a sputtering power of 80 W in Example 5 of the experimental example of the present invention.
[0024] Figure 6These are SEM images of the GaSb thin film annealed at 450, 500, 550, 600 and 650 °C for 1 h in a tubular annealing furnace under the conditions of a growth temperature of 450 °C and a sputtering power of 80 W in Example 5 of the experimental example of the present invention.
[0025] Figure 7 : These are Raman graphs of the GaSb thin films of Example 6 in the experimental examples of the present invention that were rapidly annealed at 600°C for 3, 10, 15 and 20 min under the conditions of a growth temperature of 450°C and a sputtering power of 80 W.
[0026] Figure 8 These are SEM images of GaSb films of Example 6 in the experimental examples of the present invention, which were rapidly annealed at 600°C for 3, 10, 15 and 20 min under the conditions of a growth temperature of 450°C and a sputtering power of 80 W.
[0027] Fig. 9 AFM images of the GaSb film grown at 450°C and sputtered at 80W in Example 6 of the present invention and the GaSb film rapidly annealed at 600°C for 10 min. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations. In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.
[0029] Embodiment 1,
[0030] In this embodiment, a method for preparing a GaSb thin film based on magnetron sputtering technology is provided, and this embodiment includes the following steps:
[0031] Step 1: uniformly mix simple Ga and Sb or a compound containing simple Ga and Sb in an atomic ratio of 1:1 to prepare a P-type GaSb target for use.
[0032] Step 2: Clean the gallium antimonide substrate. Place the gallium antimonide substrate on a polytetrafluoroethylene cleaning rack, place it in an ethanol solvent and use ultrasonic cleaning for 10 minutes. Then, use deionized water to clean the cleaned gallium antimonide substrate by spraying and overflowing for 10 minutes. Use acetone solution to ultrasonically clean the cleaned gallium antimonide substrate for 10 minutes. Then, use deionized water to clean the cleaned gallium antimonide substrate by spraying and overflowing for 10 minutes.
[0033] The GaSb substrate that had been cleaned twice was soaked in 5% hydrogen fluoride for 3 minutes to completely remove surface impurities and oxide layers. After soaking, it was blown dry with nitrogen.
[0034] It should be noted that the GaSb substrate in this embodiment is a single-sided polished P-type single crystal GaSb, which contains a large number of holes, which is conducive to enhancing the hole concentration in the system, improving the carrier mobility, and improving the photoelectric performance of the prepared photodetector. In this embodiment, the crystal orientation of the GaSb substrate is preferably (100). The thickness of the GaSb substrate is 500±25 μm, and the carrier concentration is 1×10 14 cm -3 . The carrier mobility is 500 cm 2 / V·s. The size of the GaSb substrate in this embodiment is a square piece of 10 mm×10 mm.
[0035] Step 3: Place the cleaned GaSb substrate on a sample tray and place it in the vacuum chamber of the magnetron sputtering machine. Evacuate the vacuum chamber until the vacuum degree reaches 1.9×10 -4 Pa, set the temperature and raise the temperature to 660 ℃ and keep it for 10 minutes.
[0036] Step 4: Lower the temperature in the vacuum chamber to 450 °C, fill the sputtering chamber with high-purity argon gas, set the argon gas flow rate to 20 sccm, and the gas pressure to 0.5 Pa.
[0037] The target material was sputtered on the surface of the GaSb substrate using a radio frequency sputtering method, with the sputtering power controlled at 50 W, the sputtering time at 30 min, and the growth temperature at 350 °C.
[0038] A GaSb film with a deposition thickness of 500 nm is obtained.
[0039] Step 5: After the magnetron sputtering, the GaSb substrate is cooled to room temperature and then annealed.
[0040] The annealing operation was carried out in an argon atmosphere with a flow rate of 50 mL / min.
[0041] The annealing temperature was 450 °C, the heating rate was 5 °C / min, and the annealing time was 90 min.
[0042] In this embodiment, using a smaller sputtering power is helpful for the sputtering growth of GaSb, and a higher annealing temperature can increase the crystallinity and uniformity of GaSb, while reducing the defect density in the film and at the interface.
[0043] Embodiment 2,
[0044] The main steps of this example are the same as those of Example 1, except that:
[0045] In this embodiment, the thickness of the GaSb substrate in step 2 is 500±25 μm, and the carrier concentration is 3×10 14 cm -3 The carrier mobility is 700 cm 2 / V·s.
[0046] In this embodiment, the argon gas flow rate in step 4 is 25 sccm. The sputtering power is controlled to be 90 W, the sputtering time is 1 min, and the growth temperature is 550° C. A GaSb film with a deposition thickness of 400 nm is obtained.
[0047] In this embodiment, the flow rate of argon gas in step 5 is 100 mL / min. The annealing temperature is 650° C., the heating rate is 15° C. / min, and the annealing time is 30 min.
[0048] Embodiment 3,
[0049] The main steps of this example are the same as those of Example 1, except that:
[0050] In this embodiment, the thickness of the GaSb substrate in step 2 is 500±25 μm, and the carrier concentration is 2×10 14 cm -3 The carrier mobility is 600 cm 2 / V·s.
[0051] In this embodiment, the argon gas flow rate in step 4 is 22 sccm. The sputtering power is controlled to be 70 W, the sputtering time is 15 min, and the growth temperature is 450° C. A GaSb film with a deposition thickness of 450 nm is obtained.
[0052] In this embodiment, the flow rate of argon gas in step 5 is 65 mL / min. The annealing temperature is 500° C., the heating rate is 10° C. / min, and the annealing time is 75 min.
[0053] Embodiment 4:
[0054] The sputtering growth equipment used in this embodiment is a TRP-450 high vacuum radio frequency multi-target sputtering coating apparatus, in which there are two DC sputtering targets and one radio frequency sputtering target in the growth chamber, and the annealing equipment used is a TL-1700 tubular annealing furnace. Figure 1 The flowchart of the GaSb thin film preparation method in this embodiment is shown. As can be seen from the figure, the specific steps of this embodiment are as follows:
[0055] 1. Evenly mix simple Ga and Sb or a compound containing simple Ga and Sb in an atomic ratio of 1:1 to prepare a P-type GaSb target for use.
[0056] Substrate cleaning: A 10 mm × 10 mm (100) oriented GaSb single crystal substrate was ultrasonically cleaned in acetone, anhydrous ethanol, and deionized water for 10 min in sequence, and finally immersed in 5% HF for 1 min to remove impurities and oxide layer on the substrate surface. It was then blown dry with nitrogen and placed in a vacuum chamber.
[0057] 2. GaSb film growth: Place the cleaned GaSb substrate into the sputtering chamber and wait until the vacuum reaches 1.9×10 -4 Pa, set the temperature and raise it to 450 °C, keep it for 20 min to degas. Then fill the sputtering chamber with high-purity argon, set the gas flow rate to 20 sccm, the gas pressure to 0.5 Pa, turn on the RF sputtering (GaSb target) power, set the sputtering power to 50 W, perform pre-sputtering for 5 min, then set the sputtering power to 80 W, and sputter for 30 min to obtain a GaSb thin film layer with a thickness of about 500 nm.
[0058] Embodiment 5:
[0059] The equipment and materials used in this embodiment are the same as those in Embodiment 4, and the specific steps are as follows:
[0060] The preparation of the GaSb substrate is the same as that of Example 4.
[0061] The growth of GaSb thin film is the same as that in Example 4.
[0062] The difference between this embodiment and embodiment 4 is that this embodiment also includes an annealing operation of the GaSb thin film sample.
[0063] The grown GaSb thin film sample was placed in a tubular annealing furnace and annealed in an Ar (purity of 5N) atmosphere with an argon flow rate of 50 mL / min, a heating rate of 10 °C / min, annealing temperatures of 450, 500, 550, 600 and 650 °C, and an annealing time of 60 min.
[0064] Embodiment 6:
[0065] The equipment and materials used in this embodiment are the same as those in Embodiment 4, and the specific steps are as follows:
[0066] The equipment and materials used are the same as those in Example 4, and the specific steps are as follows:
[0067] The preparation of the GaSb substrate is the same as that of Example 4.
[0068] The growth of GaSb thin film is the same as that in Example 4.
[0069] The difference between this embodiment and embodiment 4 is that this embodiment includes a rapid annealing operation of the GaSb thin film sample.
[0070] The grown GaSb thin film samples were placed in a rapid annealing furnace and annealed in an Ar (purity 5N) atmosphere with an argon flow rate of 50 mL / min, a heating rate of 10 ℃ / s, an annealing temperature of 500 ℃, and annealing times of 3, 10, 15, and 20 min. After cooling to room temperature, GaSb thin film samples were obtained.
[0071] Experimental example:
[0072] In this experimental example, the GaSb films prepared in Examples 4, 5, and 6 were tested under different conditions.
[0073] Figure 2 The Raman graphs of the unannealed GaSb thin films at different growth temperatures under the condition of a sputtering power of 80 W in Example 4 are shown.
[0074] In the figure, the horizontal axis of the Raman spectrum is the Raman shift (cm^-1), and the vertical axis is the Raman intensity (au).
[0075] From the five Raman spectra under different temperature conditions in the figure, it can be seen that the spectrum at a growth temperature of 350°C is characterized by a weak Raman signal and unclear peaks. This indicates that the film grown at low temperature may have a high degree of disorder and defects, resulting in a poor crystal structure and difficult to clearly distinguish Raman active modes.
[0076] The spectrum at a growth temperature of 400°C is characterized by the appearance of weaker longitudinal optical phonon (LO) mode and transverse optical phonon (TO) mode peaks, and the signal intensity has increased. This shows that the crystal quality of the film grown at 400°C has improved to a certain extent, but there are still many defects and disorder, which makes the intensity of the Raman peak relatively low.
[0077] The spectrum at a growth temperature of 450°C is characterized by a significant enhancement of the TO mode and LO mode, showing relatively clear and identifiable peaks, and the peak intensity is further improved. This shows that the crystal quality of the GaSb thin film grown at 450°C is significantly improved, the lattice order is increased, and the Raman signal is enhanced, indicating that the material structure is more perfect.
[0078] The spectrum at a growth temperature of 500°C is characterized by the continued enhancement of the peak intensities of the TO mode and the LO mode, with sharper and more symmetrical peak shapes. This indicates that the film grown at 500°C exhibits higher crystal quality, fewer defects, further increased lattice order, and stronger Raman signals.
[0079] The spectrum at a growth temperature of 550°C is characterized by the highest intensity of the TO mode and LO mode in the Raman spectrum, and the clearest peak shape. This shows that at a growth temperature of 550°C, the crystal quality of the GaSb film is optimal, the lattice order is the highest, the defects are the least, and the Raman scattering signal is the strongest.
[0080] So from Figure 2 It can be seen that with the increase of growth temperature, the intensity and clarity of the Raman signal of GaSb film are gradually enhanced. This shows that the higher the growth temperature, the better the crystal quality of the film, the higher the lattice order and the fewer defects. In the films grown at low temperatures of 350℃ and 400℃, the Raman signal is very weak, indicating poor crystal quality; while in the films grown at high temperatures of 450℃, 500℃ and 550℃, the Raman signal intensity is significantly enhanced. Especially at 550℃, the film shows the strongest and clearest Raman signal, reflecting excellent crystal quality, so this temperature may be the key temperature for optimizing the growth conditions of GaSb film.
[0081] Figure 3 The Raman graphs of the unannealed GaSb film at different sputtering powers under the growth temperature of 450° C. in Example 4 are shown.
[0082] In the figure, the horizontal axis is Raman shift (cm^-1), and the vertical axis is Raman intensity (au). From the five Raman spectra under sputtering power conditions in the figure, it can be seen that the spectrum under 50W sputtering power is characterized by significantly weaker Raman peaks, especially the longitudinal optical phonon (LO) and transverse optical phonon (TO) mode peaks are very insignificant. This shows that under low power (50 W) conditions, the crystal quality of the film is poor and the lattice is imperfect, resulting in very weak Raman signals.
[0083] The spectrum at a sputtering power of 60 W is characterized by an enhanced Raman signal, but the TO and LO mode peaks are still not obvious, and the overall signal intensity has increased only slightly. This shows that as the sputtering power increases to 60 W, the crystal quality of the film improves, but the lattice still has many defects and disorder.
[0084] The spectrum at a sputtering power of 70 W is characterized by the TO and LO modes in the Raman spectrum becoming clear and the signal intensity further increasing. This shows that when the power is increased to 70 W, the crystal quality of the film is further improved and the lattice order is improved, but it has not yet reached the optimal state.
[0085] The spectrum at 80 W sputtering power is characterized by more significant TO and LO mode peaks, significantly enhanced signal intensity, and sharper peak shape. This shows that at 80 W power, the film quality is significantly improved, the crystal structure is more perfect, the Raman signal is enhanced, and the TO and LO modes are clearly displayed.
[0086] The spectrum at a sputtering power of 90 W is characterized by the most obvious TO and LO mode peaks, the strongest signal and the sharpest spectrum peak. This shows that under high power (90 W) conditions, the film achieves the best crystal quality, the highest lattice order, the least defects, and the strongest Raman signal.
[0087] from Figure 3 It can be seen that with the increase of sputtering power, the Raman signal intensity and clarity of GaSb film gradually increase. This shows that higher sputtering power helps to improve the crystal quality and lattice order of the film. Especially at 80 W and 90 W, GaSb film shows significantly enhanced TO and LO mode Raman signals, reflecting excellent crystal quality. Therefore, at a growth temperature of 450 ° C, the structural properties of GaSb film can be significantly optimized by using high sputtering power (80 W and 90 W).
[0088] Figure 4 SEM images of unannealed GaSb films in Example 4 are shown at a sputtering power of 80 W and growth temperatures of 400, 450, 500 and 550 °C.
[0089] exist Figure 4 Figure a is a SEM image of an unannealed GaSb film grown at 400°C. It can be seen that the morphology of the GaSb film is characterized by large and irregular particles, a rough surface, and clear boundaries between particles. This shows that the GaSb film grown at a low temperature of 400°C has a large grain size and an uneven surface morphology. The large number of isolated particles indicates that the crystal quality may be poor.
[0090] b is the SEM image of the unannealed GaSb film grown at 450°C. It can be seen that the morphology of the GaSb film is that the particles are still large, but the shape is slightly more regular, the particle distribution is relatively uniform, and the surface is denser than at 400°C. This shows that after the growth temperature rises to 450°C, the grains are still large, but due to the increase in temperature, some particles begin to rearrange, and the film quality is improved.
[0091] c is the SEM image of the unannealed GaSb film grown at 500°C. It can be seen that the morphology of the GaSb film is characterized by smaller and more evenly distributed particles, a smoother surface, and blurred boundaries between particles. This shows that the GaSb film grown at 500°C has fine and evenly distributed particles, and the surface flatness is significantly improved, which indicates that the film formed at this temperature has higher quality and finer grains.
[0092] d is the SEM image of the unannealed GaSb film grown at 550℃. It can be seen that the morphology of the GaSb film is that the particles are further reduced, the surface is smoother and more uniform, and almost no individual particles can be seen. The surface is dense and has no obvious protrusions or irregular structures. This shows that the film grown at 550℃ shows the most uniform and smooth surface morphology, and the particles are extremely small, which shows that 550℃ is a relatively optimized growth temperature, which is helpful to obtain high-quality GaSb films.
[0093] from Figure 4 It can be seen that with the increase of growth temperature, the surface morphology of GaSb film changes from irregular large particles to uniform small particles. The surface particles of the film grown at low temperature (400℃ and 450℃) are large and uneven, while the surface of the film grown at high temperature (500℃ and 550℃) becomes flat and uniform. Especially at 550℃, the film surface is the most dense and smooth, with small and uniformly distributed grains. This shows that higher growth temperature helps to improve the uniformity and flatness of GaSb film, thereby improving its quality.
[0094] Figure 5 The Raman graphs of the GaSb film grown at a growth temperature of 450°C and a sputtering power of 80 W in Example 5 after annealing at 450, 500, 550, 600 and 650°C for 1 h in a tubular annealing furnace are shown.
[0095] from Figure 5 It can be seen that the TO peak of GaSb in the sample annealed at 450 °C does not change significantly compared with that before annealing, and the surface diffusion of Sb element is still very significant. Figure 6 As can be seen from Figure a, annealing at 450°C has almost no improvement on the quality of GaSb films.
[0096] The characteristic peak of Sb in the sample annealed at 500°C is enhanced, and the blue shift of the characteristic peak proves that the surface diffusion of Sb element causes compressive stress on the film surface. Figure 6 As can be seen from Figure b, a film is formed on the surface of the sample, but the Sb element diffused on the surface is the main element.
[0097] The characteristic peak of Sb element in the sample annealed at 550℃ is enhanced and broadened, and the surface diffusion of Sb element is intensified. Figure 6 As can be seen from Figure c, the GaSb on the sample surface appears island-shaped due to the high temperature, and the flatness of the film decreases.
[0098] The half-width of the characteristic peak of the Sb element in the sample annealed at 600°C decreases, the crystallinity of the surface Sb element increases, and after reaching the GaSb recrystallization temperature, the TO feature is significantly enhanced. Figure 6As can be seen from Figure d, GaSb on the sample surface has obvious holes due to high-temperature recrystallization, which destroys the surface of the film sample.
[0099] Figure 6 SEM images of the GaSb film grown at a growth temperature of 450°C and a sputtering power of 80 W in Example 5 after annealing at 500, 550, 600 and 650°C for 1 h in a tubular annealing furnace are shown.
[0100] exist Figure 6 Figure a is a SEM image of GaSb film annealed at 500°C. It can be seen from the figure that its surface is relatively flat and uniform, and the particles are small and densely distributed. This shows that at the annealing temperature of 500°C, the surface maintains good flatness and the particles are relatively small, indicating that the grain growth at this temperature is relatively limited.
[0101] b is the SEM image of GaSb film annealed at 550℃. It can be seen from the figure that its surface remains flat and the particles are slightly larger than 500℃, but still uniformly distributed. This shows that at the annealing temperature of 550℃, the grains begin to grow slightly, but the overall morphology does not change much, indicating that annealing has little effect on the surface morphology of the film.
[0102] c is the SEM image of GaSb film annealed at 600℃. It can be seen from the figure that its surface becomes rougher, the particles become larger, and the boundaries between particles become clearer. This shows that at the annealing temperature of 600℃, the grain growth is accelerated, resulting in the increase of surface particles and the roughening of the surface, which is the result of grain growth.
[0103] d is the SEM image of GaSb film annealed at 650℃, from which we can see that: the surface is greatly roughened, the particles become more obvious and significantly larger, and even particles aggregate. This shows that at the high annealing temperature of 650℃, the grain growth and rearrangement are very obvious, the surface morphology changes significantly, and there may be larger aggregation areas and voids, and the surface is irregular and more complex.
[0104] From the whole Figure 6 It can be seen that with the increase of annealing temperature, the surface morphology of GaSb film gradually changes from flat to rough, and the particle size gradually increases from fine and uniform to form aggregation. This shows that high temperature annealing has a significant effect on the growth and rearrangement of grains, and high temperature promotes the growth of grains and the rearrangement of interfaces. These changes have an important influence on the electronic and optical properties of the material. According to the required performance, the morphological characteristics of the film can be controlled by adjusting the annealing temperature.
[0105] Figure 7The Raman graphs of the GaSb thin film in Example 6, which was rapidly annealed at 600°C for 3, 10, 15 and 20 min under the conditions of a growth temperature of 450°C and a sputtering power of 80 W, are shown.
[0106] from Figure 7 It can be seen that the characteristic peaks of the sample rapidly annealed at 600 °C for 3 min do not change significantly before and after annealing, showing an uneven distribution. Figure 8 As can be seen from Figure a, the sample rapidly annealed at 600 °C for 3 min becomes thin film, and voids appear on the surface of the film due to the high temperature.
[0107] The TO characteristic peak of the sample rapidly annealed at 600 °C for 10 min is significant. Rapid annealing can effectively inhibit the surface diffusion of Sb elements, which is beneficial to the improvement of the crystallinity of the film. Figure 8 As can be seen in Figure b, there are a few holes on the surface of the sample that was rapidly annealed at 600°C for 10 min, and the film quality is relatively high. Fig. 9 It can be found that the surface roughness of the sample after rapid retreat treatment decreased from 8.44 nm to 2.488 nm, and a film with higher surface flatness was obtained.
[0108] The TO characteristic peak of the sample rapidly annealed at 600℃ for 15 min remains almost unchanged, and the effect of the extended annealing time on the crystallinity of GaSb is weakened. Figure 8 As can be seen from Figure c, holes appear on the surface of the sample that was rapidly annealed at 600 °C for 15 min, and the number of defects increases.
[0109] The half-width of the TO characteristic peak of the sample rapidly annealed at 600℃ for 20 min hardly changes, and the extension of annealing time no longer affects the crystallinity of GaSb. Figure 8 As can be seen from Figure d, the sample surface undergoes irreversible damage after rapid annealing at 600 °C for 20 min, and the film quality decreases.
[0110] Figure 8 The SEM images of the GaSb film in Example 6 with a growth temperature of 450 °C and a sputtering power of 80 W at 600 °C for rapid annealing for 3, 10, 15 and 20 min are shown. In the figure a, rapid annealing for 3 minutes is shown. It can be seen that the surface of the film with rapid annealing for 3 minutes is relatively flat, the particle distribution is relatively uniform, and the particle density is low. This indicates that short-term annealing may not be sufficient to cause significant grain rearrangement or growth.
[0111] Figure b is a 10-minute rapid annealing. It can be seen that the particle density increases after 10 minutes of rapid annealing, the particle size increases slightly, and the surface remains relatively uniform. In other words, as the annealing time increases, the grains begin to grow and rearrange, and the surface particles become more obvious.
[0112] Figure c is a rapid annealing for 15 minutes. It can be seen that the particles of rapid annealing for 15 minutes become more obvious, the particle size continues to increase, and the particle distribution in different areas is not uniform. At this stage, the grain growth is more significant, the surface becomes rougher, and particle groups of different sizes may be formed.
[0113] Figure d is a rapid annealing for 20 minutes. It can be seen that the surface particle size of the rapid annealing for 20 minutes has increased significantly, the particle distribution has become more uneven, and obvious aggregation and growth have appeared in local areas. This shows that long-term annealing has led to significant grain growth and rearrangement, and the surface morphology has changed most significantly, and larger grains or agglomeration may have appeared.
[0114] Fig. 9 AFM images of the GaSb film grown at a temperature of 450° C. and a sputtering power of 80 W and the GaSb film rapidly annealed at 600° C. for 10 min in Example 6 are shown.
[0115] Figures a and b show the surface morphology of GaSb films without annealing and after rapid annealing at 600 °C for 10 minutes, respectively.
[0116] Figure a shows the surface morphology of the unannealed GaSb film, from which it can be seen that the surface is relatively rough, with obvious linear or scratch structures. The surface particles are distributed evenly, but relatively uneven. At the same time, the regional root mean square roughness (RMS) is 8.44 nm. This value is large, indicating that the surface roughness is high, with large morphological fluctuations and unevenness.
[0117] Figure b shows the surface morphology of the GaSb film that was rapidly annealed at 600°C for 10 minutes. It can be seen that the surface has become smoother, the particle size has decreased, and the distribution has become more uniform. A small number of higher particles or protrusions are more dispersed. At the same time, the regional root mean square roughness (RMS) is 2.488 nm. Compared with the unannealed sample, this value is significantly reduced, indicating that the surface flatness has been significantly improved and the morphology is smoother.
[0118] Therefore, it can be seen from the figure that the surface morphology of the GaSb film after rapid annealing at 600 ° C for 10 minutes has changed significantly. The surface of the unannealed film is rough and has obvious scratches, while the surface of the annealed film becomes smooth and the particle distribution is more uniform. This shows that the annealing process helps to flatten the film surface and rearrange the particles, thereby reducing the roughness and improving the film quality. In electronic and optoelectronic applications, surface flatness and uniformity are very important, so the annealing treatment of the present invention has a good effect on the performance optimization of the GaSb film.
[0119] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing GaSb thin film based on magnetron sputtering technology, characterized in that: The preparation method comprises: Prepare magnetron sputtering target material for use, soak the GaSb substrate in ethanol solvent, use ultrasonic cleaning for 10 minutes, and then use deionized water to clean the GaSb substrate for 10 minutes. Then, the gallium antimonide substrate was immersed in an acetone solution and cleaned with ultrasonic waves for 10 minutes, and then the gallium antimonide substrate was cleaned with deionized water for 10 minutes; The cleaned GaSb substrate was sent to the magnetron sputtering machine, and the vacuum degree of the sputtering chamber of the magnetron sputtering machine was controlled at 1.9×10 -4 Pa, and at the same time, the sputtering chamber was heated to 660 °C and kept at this temperature for 10 min; The temperature of the sputtering chamber is lowered to 450°C to sputter the target material on the surface of the gallium antimonide substrate, forming a GaSb film on the surface of the gallium antimonide substrate, and obtaining a GaSb film with a deposition thickness of 400-500 nm.
2. The method for preparing GaSb thin film based on magnetron sputtering technology according to claim 1, characterized in that: The magnetron sputtering target is a P-type GaSb target prepared by uniformly mixing simple Ga and Sb or a compound containing simple Ga and Sb in an atomic ratio of 1:
1.
3. The method for preparing GaSb thin film based on magnetron sputtering technology according to claim 1, characterized in that: The gallium antimonide substrate is a single-side polished P-type single crystal gallium antimonide.
4. According to the method for preparing GaSb thin film based on magnetron sputtering technology as claimed in claim 1, the sputtering target is sputtered by radio frequency sputtering method.
5. The method for preparing GaSb thin film based on magnetron sputtering technology according to claim 1, characterized in that: The sputtering power of the magnetron sputtering device is 50-90 W, the sputtering time is 1-30 min, the growth temperature is 350-550 ° C, the working gas during sputtering is argon, the gas flow rate is 20-25 sccm, and the gas pressure is 0.5 Pa.
6. The method for preparing GaSb thin film based on magnetron sputtering technology according to claim 1, characterized in that: The preparation method further comprises an annealing step, wherein the gallium antimonide substrate after magnetron sputtering is cooled to room temperature and then annealed.
7. The method for preparing GaSb thin film based on magnetron sputtering technology according to claim 6, characterized in that: The annealing operation is carried out in an argon atmosphere with a flow rate of 50-100 mL / min.
8. The method for preparing GaSb thin film based on magnetron sputtering technology according to claim 6, characterized in that: The annealing operation has an annealing temperature of 450-650°C, a heating rate of 5-15°C / min, and an annealing time of 30-90 min.